PbS/CdS/ZnS Quantum Dots: A Multifunctional Platform for In Vivo Near-Infrared Low-Dose Fluorescence Imaging - Benayas, Antonio; Ren, Fuqiang; Carrasco, Elisa; Marzal, Vicente; del Rosal, Blanca; Gonfa, Belete A.; Juarranz, Ángeles; Sanz-Rodríguez, Francisco; Jaque, Daniel; García-Solé, José; Ma, Dongling; Vetrone, Fiorenzo (Advanced functional materials, 2015)
Over the past decade, near‐infrared (NIR)‐emitting nanoparticles have increasingly been investigated in biomedical research for use as fluorescent imaging probes. Here, high‐quality water‐dispersible core/shell/shell PbS/CdS/ZnS quantum dots (hereafter QDs) as NIR imaging probes fabricated through a rapid, cost‐effective microwave‐assisted cation exchange procedure are reported. These QDs have proven to be water dispersible, stable, and are expected to be nontoxic, resulting from the growth of an outer ZnS shell and the simultaneous surface functionalization with mercaptopropionic acid ligands. Care is taken to design the emission wavelength of the QDs probe lying within the second biological window (1000–1350 nm), which leads to higher penetration depths because of the low extinction coefficient of biological tissues in this spectral range. Furthermore, their intense fluorescence emission enables to follow the real‐time evolution of QD biodistribution among different organs of living mice, after low‐dose intravenous administration. In this paper, QD platform has proven to be capable (ex vivo and in vitro) of high‐resolution thermal sensing in the physiological temperature range. The investigation, together with the lack of noticeable toxicity from these PbS/CdS/ZnS QDs after preliminary studies, paves the way for their use as outstanding multifunctional probes both for in vitro and in vivo applications in biomedicine. Low‐dose in vivo near‐infrared (NIR) fluorescence imaging is achieved by using carefully designed PbS/CdS/ZnS quantum dots (QDs), intensely emitting within the second biological window (1000–1350 nm). Moreover, preliminary studies both in vitro and in vivo have proven the lack of noticeable toxicity of these QDs. As an additional advantage, this NIR‐fluorescence imaging platform has demonstrated useful multifunctionality, thus being capable, both ex vivo and in vitro, of high‐resolution thermal sensing in the physiological temperature range.